To simplify the expression \( \frac{2^2}{2^{-4}} \) using the properties of integer exponents, we can apply the quotient property of exponents, which states:
\[ \frac{a^m}{a^n} = a^{m-n} \]
In this case, let \( a = 2 \), \( m = 2 \), and \( n = -4 \). Therefore, we can rewrite the expression as:
\[ \frac{2^2}{2^{-4}} = 2^{2 - (-4)} = 2^{2 + 4} = 2^6 \]
Now, we can express \( 2^6 \) as a whole number:
\[ 2^6 = 64 \]
Thus, the solution to the expression \( \frac{2^2}{2^{-4}} \) is:
\[ \boxed{64} \]